Titanium Dioxide Wrapped MOFs-Derived Cobalt-Doped Porous Carbon Polyhedrons as Sulfur Hosts for Advanced Lithium–Sulfur Batteries. Issue 200 (24th July 2019) - Li, Miaomiao; Feng, Wangjun; Su, Wenxiao; Song, Changkun; Chen, Linjing
Abstract: To overcome the shortcomings (low-activity materials and the poor cycle stability) of lithium-sulfur (Li-S) batteries, rational design of cathode host materials is critical. Herein, we developed core-shellCo@NPC@TiO2 nanostructures, coating titanium dioxide (TiO2 ) on cobalt-doped nanoporous carbon (Co@NPC) derived from the thermal decomposition of zeolitic imidazolate framework-67 (ZIF-67) for sulfur electrodes. The synthesized Co@NPC@TiO2 has excellent electrical conductivity and strong restrictions on polysulfides, the sulfur cathodes with core-shell structure demonstrate a high initial discharge capacity of 1400 mAh g −1 at 0.1 C, compared with porous carbon, the electrical conductivity and cyclic stability are improved obviously.